29.30.22 problem 882

Internal problem ID [5462]
Book : Ordinary differential equations and their solutions. By George Moseley Murphy. 1960
Section : Various 30
Problem number : 882
Date solved : Monday, January 27, 2025 at 11:24:45 AM
CAS classification : [[_1st_order, _with_linear_symmetries], _Clairaut]

\begin{align*} \left (1+3 x \right ) {y^{\prime }}^{2}-3 \left (y+2\right ) y^{\prime }+9&=0 \end{align*}

Solution by Maple

Time used: 0.089 (sec). Leaf size: 51

dsolve((1+3*x)*diff(y(x),x)^2-3*(2+y(x))*diff(y(x),x)+9 = 0,y(x), singsol=all)
 
\begin{align*} y \left (x \right ) &= -2-2 \sqrt {3 x +1} \\ y \left (x \right ) &= -2+2 \sqrt {3 x +1} \\ y \left (x \right ) &= \frac {9+\left (3 x +1\right ) c_{1}^{2}-6 c_{1}}{3 c_{1}} \\ \end{align*}

Solution by Mathematica

Time used: 0.015 (sec). Leaf size: 60

DSolve[(1+3 x) (D[y[x],x])^2-3(2+y[x])D[y[x],x]+9==0,y[x],x,IncludeSingularSolutions -> True]
 
\begin{align*} y(x)\to c_1 \left (x+\frac {1}{3}\right )-2+\frac {3}{c_1} \\ y(x)\to \text {Indeterminate} \\ y(x)\to -2 \left (\sqrt {3 x+1}+1\right ) \\ y(x)\to 2 \left (\sqrt {3 x+1}-1\right ) \\ \end{align*}